Professor Alexander Zawadzki of Lvov university – Gregor Mendel’s mentor and inspirer - Szybalski, W. (Вiopolymers and Cell, 2010)
It is generally agreed that Johann Gregor Mendel (1822–1884) is the undisputed father of genetics, the study of heredity that is fundamental to our understanding of all living things. However, as a geneticist and engineer, strongly influenced by my teachers in Lvov and Gdansk, in Copenhagen and in Cold Spring Harbor (NY), I have always wondered how it was possible for Mendel to be such an independent thinker while not having a mentor who could have guided his creative and analytical thinking. Was there anybody in Mendel’s life who could have played this role? At the very least, did he get any opportunity to discuss his experimental designs with some colleague or to receive any help from a mentor or a friend in analyzing his results? The purpose in preparing this essay is to bring to light a long neglected story of how an «obscure Polish Professor from Lvov University», Alexander Zawadzki, played a critical role in helping an «obscure Austrian monk», Gregor Mendel, to create the discipline of genetics. Загальновизнано, що Іоганн Грегор Мендель є фундатором генетики – науки, яка вивчає спадковість, що є основою для розуміння всіх життєвих процесів. Однак як генетик, що перебував під впливом моїх вчителів у Львові і Гданьську, Копенгагені і Коулд Спрінг Харборі (Нью-Йорк), я завжди дивувався, як вдалося Менделю бути таким незалежним мислителем за відсутності у нього наставника, який міг би спрямувати його відкриття та аналітичний розум? Чи був хтось у житті Менделя, хто займав таке положення? У крайньому разі, чи була у ньго можливість обговорювати свої експерименти з кимось із колег та одержувати допомогу від керівника або друга в аналізі отриманих результатів? У представленій статті зроблено спробу висвітлити історичні факти, які довгий час перебували в тіні, як маловідомий польський професор із Львівського університету Александр Завадські допоміг непомітному австрійському ченцю Менделю започаткувати основи генетики. Общепризнано, что Иоганн Грегор Мендель является основателем генетики – науки, изучающей важнейшее для понимания всех жизненных процессов явление – наследственность.Однако как генетик, находящийся под влиянием моих учителей во Львове и Гданьске, Копенгагене и Коулд Спринг Харборе (Нью- Йорк), я всегда удивлялся, как удалось Менделю быть таким независимым мыслителем при отсутствии у него наставника, способного направить его открытия и аналитический ум? Был ли кто-нибудь в жизни Менделя, кто занимал такое положение? В крайнем случае, была ли у него возможность обсуждать свои эксперименты с кем-нибудь из коллег и получать помощь от руководителя или друга при анализе полученных результатов? В представленной статье сделана попытка осветить долгое время находившиеся в тени истории факты, как малоизвестный польский профессор Львовского университета Александр Завадски помог незаметному австрийском монаху Менделю создать основы генетики.